Critical Atomic-level Processing Technologies: Remote Plasma-enhanced Atomic Layer Deposition and Atomic Layer Etching - Yuan, Guangjie; Li, Haohao; Shan, Bo; Liu, Johan (Micro and Nanosystems, 2018)
As feature sizes of devices shrink every year, deposition and etching processes change to be very challenge, especially for sub-7 nm technology node. The acceptable variability of feature size is expected to be several atoms of silicon/germanium in the future. Therefore, Remote Plasma-Enhanced Atomic Layer Deposition (RPE-ALD) and Atomic Layer Etching (ALE) change to be more and more important in the semiconductor fabrication. Due to their self-limiting behavior, the atomic-scale fidelity could be realized for both of them in the processes. Compared with traditional Physical Vapor Deposition (PVD) and Chemical Vapor Deposition (CVD) methods, atomic-scale thickness controllability and good conformality can be achieved by RPE-ALD. Unlike conventional plasma etching, atomicscale precision and excellent depth uniformity can be achieved by ALE. The fundamentals and applications of RPE-ALD and ALE have been discussed in this paper. Using the combination of them, atomic-level deposition/etch-back method is also mentioned for achieving high quality ultra-thin films on three dimensional (3D) features.
Keywords: Plasma-enhanced atomic layer deposition